(untitled) - Andrews, Mary Kay; 1954- (New York, 2024)
"Welcome to the St. Cecelia, a landmark hotel on the coast of Georgia, where traditions run deep and scandals run even deeper. . . . Everyone refers to the St. Cecelia as "the Saint." If you grew up coming here, you were "a Saint." If you came from the wrong side of the river, you were "an Aint." Traci Eddings was one of those outsiders whose family wasnt rich enough or connected enough to vacation here. But she could work here. One fateful summer she did, and married the bosss son. Now, shes the widowed owner of the hotel, determined to see it return to its glory days, even as staff shortages and financial troubles threaten to ruin it. Plus, her greedy and unscrupulous brother-in-law wants to make sure she fails. Enlisting a motley crew of recently hired summer help- including the daughter of her estranged best friend-Traci has one summer season to turn it around. But new information about a long-ago drowning at the hotel threatens to come to light, and the tragic death of one of their own brings Traci to the brink of despair. Traci Eddings has her back against the pink-painted wall of this beloved institution. And it will take all the wits and guts she has to see wrongs put to right, to see guilty parties put in their place, and maybe even to find a new romance along the way."--
Keywords: Women; Fiction; Summer; Fiction; Vacations; Fiction; Georgia; Fiction; Novels